Investigação química de extratos de bactérias marinhas associadas ao sedimento do arquipélago de São Pedro e São Paulo - Silva, Alison Batista da (2016)
The present work describes the chemical investigation of two active bacteria strains identified as Salinispora arenicola (BRA-213) and Streptomyces sp. (BRA-199), both isolated from sediments of Saint Peter and Saint Paul’s Archipelago – State of Pernambuco. From S. arenicola were isolated six compounds: 3-hydroxy-6-methoxy-N-methylindolin-2-one, 6-methoxy-N-methyl-isatin, N-acetyl-β-oxo-tryptamine, saliniketal A, 4-(2’-oxopropyl)-3-oxorifamycin S and 27-demethoxy-27-hydroxy-4-(2’-oxopropyl)-3-oxorifamycin S. In addition, three staurosporines (staurosporine, N-methyl-staurosporine, and hydroxy-N-methyl-staurosporine) were identified by LC-MS and research in the AntiMarin database which are responsible for the cytotoxic activity of S. arenicola extract (IC50 0.55 µg/mL). Among the isolated compounds the rifamycins are been reported for the first time and the compounds 3-hydroxy-6-methoxy-N-methyl indolin-2-one and 6-methoxy-N-methyl-isatin are recorded first from microorganisms. From Streptomyces sp. were isolated the compounds piericidin A, cyclo-hydroxy-Pro-Leu, cyclo-Trp-Pro, cyclo-Phe-Pro while compound glicopiericidin, also was identified by LC-MS and AntiMarin database. The structures of the isolated compounds were determined by the interpretation of its 1H and 13C NMR (1D and 2D) and mass spectrometry. Piericidin A showed cytotoxic activity justifying the activity exhibited by the extract of Streptomyces sp. (IC50 0.07 µg/mL).